Validating scales for measuring the influence of social responsibility behavior and organizational culture on employee performance in the Ghanaian context - Ntumi, Simon; Nimo, Daniel Gyapong; Yeobah, Abraham; Tetteh, Alex; Akuffo Boateng, Dorothy; Daniel Kuupile, Dortuo; Sewaa Antwi, Esther (Open Science Journal, 2024)
Aims: The study sought to validate scales for measuring the influence of social responsibility behavior and organizational culture on the employee performance in the Ghanaian context. Methods: The study utilised a cross-sectional design and relied on previously developed instruments related to the variables of interest. The study collected data from 250 employees in Ghana. The analysis was performed using inferential statistics such as ANOVA, Pearson correlation and ordinal logistic regression (OLR). Findings: The study established standard scales for measuring social responsibility behavior and organizational culture on employee performance in Ghanaian context. Based on the tested hypotheses, it was found that one-unit increase in conscientiousness had a significant influence on the probability of observing a higher category of employee performance (B = 0.691, x2=15.299, p=0.002). Altruism had no significant influence on the probability of observing a higher category of employee performance (B= 0.036, x2 = 0.63, p=0.802). Conscientiousness had a significant influence on the probability of observing a higher category of employee performance (B= 0.683, x2 = 15.847, p=0.000). Furthermore, organisational culture had a significant influence on the probability of observing a higher category of employee performance (B= 0.683, x2 = 15.847, p=0.000). Recommendations: It was recommended that in every organization, management and human resource personnel should take into account organizational social responsibility behavior and culture when designing frameworks that aimed at enhancing employee performance within the organization.